Analysis of the Impact of the Use of Electronic Money on Community Consumption Behavior in The Bogor Station Environment - Mochammad Rizky Kusumayudha; Ahmad Hafidzul Kahfi; Muhamad Hasan; Fitra Septia Nugraha (Institute of Computer Science (IOCS), 2022)
With the existence of non-cash payment instruments such as electronic money (e-money), which is part of the new policy in the payment system by Bank Indonesia, it will be able to optimize people's purchasing power which at the same time has an impact on improving the country's economy. This non-cash payment system makes it easier for people to transact. As happened in several cases regarding the effect of using e-money on people in Indonesia, namely the increase in consumptive behavior and the difficulty of saving when they have more than enough money for their daily needs. The method used by the author to obtain the necessary data is by observation, interviews, and literature study. The results of the analysis of this problem are to find out what impacts can affect the behavior of people who use e-money, as well as precautions that can be taken to reduce the impact and influence of using e-money.